Sectoral Contributions to Labour Productivity Growth - Bev Dahlby (The School of Public Policy Publications)
Addressing Canada’s slow productivity growth has become a public policy priority. However, this paper argues that declines or slower growth in aggregate labour productivity should not automatically be interpreted as a deterioration in living standards. Improvements in an economy’s terms of trade also play a crucial role in advancing living standards. Low rates of productivity growth may, in some cases, result from welfare-enhancing reallocations of labour into sectors with lower labour productivity.